COGNITIVE AND LINGUOPRAGMATIC PROBLEMS OF PERCEPTION VERBS IN ENGLISH AND UZBEK LANGUAGES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The problem of perception is one of the important problems in the study of man. Man's ability to perceive the real world is one of his fundamental abilities along with feeling, imagining, thinking, understand. Information about the surrounding world is provided to a person in a directly sensory form by a variety of colours, sounds, tastes, smells. This article gives information about cognitive and linguopragmatic problems of perception verbs in English and Uzbek languages.